2004
DOI: 10.1007/s11099-005-0010-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phosphorus and nitrogen on photosynthetic parameters and growth in Vicia faba L.

Abstract: The influence of phosphorus (P) and nitrogen (N) supply on biomass, leaf area, photon saturated photosynthetic rate (P max ), quantum yield efficiency (α), intercellular CO 2 concentration (C i ), and carboxylation efficiency (CE) was investigated in Vicia faba. The influence of P on N accumulation, biomass, and leaf area production was also investigated. An increase in P supply was consistently associated with an increase in N accumulation and N productivity in terms of biomass and leaf area production. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…2). Similar reductions have been observed in P‐deficient tea (Salehi and Hajiboland, 2008), sugar beets (Rao et al, 1990), common bean (Nielsen et al, 2001), faba bean ( Vicia faba L.) (Jia and Gray, 2004, 2007), and maize leaves (Khamis et al, 1990). Effects of P deficiency on leaf photosynthetic capacity at saturating irradiance were also observed on the A‐Ci responses (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…2). Similar reductions have been observed in P‐deficient tea (Salehi and Hajiboland, 2008), sugar beets (Rao et al, 1990), common bean (Nielsen et al, 2001), faba bean ( Vicia faba L.) (Jia and Gray, 2004, 2007), and maize leaves (Khamis et al, 1990). Effects of P deficiency on leaf photosynthetic capacity at saturating irradiance were also observed on the A‐Ci responses (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…This purported control over rate limiting steps is consistent with the reduction in J max with P treatment in Table 2. Although Rao and Terry (1989) did not measure a reduction in its activity, Brooks (1986) and Brooks et al (1988) observed reduced RuBisCo carboxylase content in P-defi cient leaves and Jia and Gray (2004) observed a decrease in V cmax with declining P supply in faba bean, reasoning that P supply infl uenced the rate of RuBisCo carboxylase activation, a phenomena likely related to the present observations. In the present case, leaf N concentration did not decline with soil P (Fig.…”
Section: Leaf Gas Exchangementioning
confidence: 47%
See 1 more Smart Citation
“…Phosphorus deficiency decreases photosynthetic electron transport capacity by impairing the electron transport chain. Such impairment decreases ATP content, which in turn limits RuBP regeneration and therefore the rate of CO 2 assimilation (Jia and Gray 2004;Lin et al 2009). This may explain the positive relationship between V c-max and P. In addition, the supply of inorganic P regulates the Calvin cycle and the transport of metabolic and assimilated compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its catalytic role, it has been suggested that under high availability of nitrogen, Rubisco can function as a storage protein (Warren et al 2003;Warren 2004). Although several studies have been conducted on the effect of nutrient on photosynthesis (Jia and Gray 2004;Hidaka and Kitayama 2009), specific information about the in situ nutrient-photosynthesis relationship of Amazonian trees is still sparse (Mendes et al 2013). In this study, we hypothesized that under the ambient conditions of the forest understory, photosynthesis, V c-max and J max may be limited by the availability of nutrients and that species with low leaf nutrient content are able to use them parsimoniously.…”
mentioning
confidence: 99%